Assessment of the Quality Indicators of the Carriage Movement by Directly Measuring the Forces of Interaction between the Wheels and Rails - Fomin, Oleksij; Prokopenko, Pavlo (Communications - Scientific Letters of the University of Zilina, 2024)
This work describes the features and methods of measuring the forces of interaction between the wheel pairs and rails by measuring wheel deformations at control points. The work also contains recommendations for direct measurements of the forces of interaction between the wheels and rails to determine the actual margin of stability of wheel pairs from derailment. The result of the work is general requirements for the system of direct measurement of the strength of interaction of the high-speed rolling stock wheel pairs with rails and scientifically based recommendations for direct measurement of the interaction forces of wheels and rails. The problems of interaction between the wheel pairs and rails do not significantly depend on the track width and are general in nature for different countries of the world.
Keywords: contact of wheels with rails; control; interaction indicators; rolling stock; traffic safety